Unions and Technology: A Survey of Union Use of Information Technology - Templer, Andrew; Solomon, Norman (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1988)
The purpose of this study is to investigate the extent to which unions in Canada use information technology, the types of technology used, the way in which the technology is implemented, the general level of satisfaction with the new methods and proposals for the implementation of new methods in the future.